The Paris Agreement 2015: Turning point for the international climate regime - Susanne Dröge (Stiftung Wissenschaft und Politik (SWP), 2016)
At the Paris climate summit in December 2015 the 196 parties to the United Nations Framework Convention on Climate Change (UNFCCC) established a new international climate policy regime from 2020 onwards. The Paris Agreement includes how to proceed with protecting the climate (mitigation), how to adapt to climate change (adaptation), and how to handle potential loss and damage, technology transfer and climate finance. The Nationally Determined Contributions (NDCs) are recognised internationally as each country's way forward in mitigation and adaptation actions. Amongst the UNFCCC parties a key differentiation remains: developed countries are asked to act ambitiously and fast on mitigation, and to support developing countries financially and technically to deliver on their NDCs. For the first time, the participation in international climate policy is comprehensive, and accounting rules and transparency requirements for emissions data will apply to all countries in the same manner after 2020. Regular reviews will take place every five years in order to motivate an increase in ambitions towards the global temperature limit of 2 degrees Celsius and the financial commitments. The research paper elaborates how negotiations and the international energy and climate policy settings evolved since the Copenhagen climate summit and how the 21st Conference of the Parties (COP21) in Paris was prepared. It examines the national climate policy and climate diplomacy activities of the United States, China, India and the European Union as well as the building blocks of the new regime. The Paris Agreement sets a framework for an effective regime. Germany and the European Union will have to follow up in 2016 with own measures and with shaping further details of the regime. (SWP Research Paper)
Keywords: 320